Combined Silicon-Phosphorus Fertilization Affects the Biomass and Phytolith Stock of Rice Plants - Li, Zimin; Guo, Fengshan; Cornelis, Jean-Thomas; Song, Zhaoliang; Wang, Xudong; Delvaux, Bruno (Frontiers in Plant Science, 2020)
Phytoliths are silica bodies formed in living plant tissues. Once deposited in soils through plant debris, they can readily dissolve and then increase the fluxes of silicon (Si) towards plants and/or watersheds. These fluxes enhance Si ecological services in agricultural and marine ecosystems through their impact on plant health and carbon fixation by diatoms, respectively. Fertilization increases crop biomass through the supply of plant nutrients, and thus may enhance Si accumulation in plant biomass. Si and phosphorus (P) fertilization enhance rice crop biomass, but their combined impact on Si accumulation in plants is poorly known. Here, we study the impact of combined Si-P fertilization on the production of phytoliths in rice plants. The combination of the respective supplies () of 0.52 g Si kg–1 and 0.20 g P kg-1 generated the largest increase in plant shoot biomass (leaf, flag leaf, stem and sheath), resulting in a 1.3-fold increase compared the control group. Applying combined Si-P fertilizer did not affect the content of organic carbon (OC) in phytoliths. However, it increased plant available Si in soil, plant phytolith content and its total stock (mg phytolith pot-1) in dry plant matter, leading to the increase of the total amount of OC within plants. In addition, P supply increased rice biomass and grain yield. Through these positive effects, combined Si-P fertilization may thus address agronomic (e.g., sustainable ecosystem development) and environmental (e.g., climate change) issues through the increase in crop yield and phytolith production as well as the promotion of Si ecological services and OC accumulation within phytoliths.